2017
DOI: 10.1891/1541-6577.31.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Physicians’ Perspectives Regarding Nurse–Physician Professional Communication: Implications for Nurses

Abstract: Nurses need to be informed of the perspectives and experiences of physicians on professional communication. Our findings can improve nurses' understandings of professional communication that could inform the development of educational and training programs for nurses and physicians. There is a need to incorporate communication courses during degree education and design interprofessional training regarding communication in clinical settings to improve teamwork and patient care. Open discussions between nurses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This study, which investigates physicians’ perception of their professional communication with nurses in Iran, reports that, in clinical procedures, physicians often trust nurses’ reports and rely on their insight in diagnoses and treatments. Physicians consider specialized knowledge, professional skill, and the ability to manage critical conditions as facilitators in professional communication and prefer to work with informed nurses [ 36 – 38 ]. It was also found that, regardless of their personality traits, physicians with higher education have a higher opinion of the value of professional communication and values, while, regardless of their personality traits, personnel with higher education are more likely to find themselves in conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…This study, which investigates physicians’ perception of their professional communication with nurses in Iran, reports that, in clinical procedures, physicians often trust nurses’ reports and rely on their insight in diagnoses and treatments. Physicians consider specialized knowledge, professional skill, and the ability to manage critical conditions as facilitators in professional communication and prefer to work with informed nurses [ 36 – 38 ]. It was also found that, regardless of their personality traits, physicians with higher education have a higher opinion of the value of professional communication and values, while, regardless of their personality traits, personnel with higher education are more likely to find themselves in conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…This study, which investigates doctors' perception of their professional communication with nurses in Iran, reports that, in clinical procedures, doctors often trust nurses' reports and rely on their insight in diagnoses and treatments. Doctors consider specialized knowledge, professional skill, and the ability to manage critical conditions as facilitators in professional communication and prefer to work with informed nurses (34,35) (36). It was also found that, regardless of their personality traits, doctors with higher education have a higher opinion of the value of professional communication and values, while, regardless of their personality traits, personnel with higher education are more likely to nd themselves in con icts.…”
Section: Discussionmentioning
confidence: 99%
“…The domestic literature mainly focuses on quantitative research on communication methods such as SBAR, D&M model, CHAT and CICARE (Shen et al, 2014), while foreign countries have numerous qualitative documents from nurses and doctors. From the perspective of communication, Schmalenberg and Kramer synthesized six qualitative researches on the nurses' experience to explore how nurses could communicate with doctors to improve the quality of patient care (Esmaeilpour‐Bandboni, Vaismoradi, Salsali, Snelgrove, & Sheldon, 2017). The phenomenological study of domestic night shift work (Xia, Hu, Li, Li, & Yu, 2005) found psychological stress of nurses' night shift communication with doctors to be an important source of psychological load, and that doctors sometimes had no response when the night nurses called.…”
Section: Introductionmentioning
confidence: 99%